Artemídia influente: ateliê-laboratório nas interfaces Arte, Ciência e Tecnologia - Matta, Célio Martins da [UNESP] (2016)
The end result of this doctoral work (thesis) presents the work format equivalent used as submission of the mentees participating in the research group "Artmedia and VideoClip". The Robust report (thesis) complements the work equivalent of a work of art in the shape of a cube of 21 cm. This major hub withdraw Ten cubes gradually lower to the extent of 11 cm, designed and built fractionally in their sockets. The textual elements are divided into chapters on the six faces of the ten cubes, allowing plurivocal reading likened to a hyperlink and can be read in any order in the ten planks generated by "deconstruction planned" cubes made possible by the joint faces. The booklet, called Catalog, containing the elements pre and post-textual academic work, highlighting in Appendix form the artistic and scientific prototypes (two exhibitions and two works of art). Artistic works are the result of research, studies, discussions and presentations that took place throughout the process of studies on art science and technology. The artistic and scientific writing used reflects the author's experience (artist-researcher) in workshops, laboratories and also in designing and delivering, seeking understanding and application of the dichotomies created (design-materialization and intuitive-rational) and their derivatives. It uses the key idea that the studio-laboratory is the place of trial.